ADVANCES IN NONINVASIVE FOOD ANALYSIS - Khan, Muhammad Kashif Iqbal ([S.l.] : CRC PRESS, 2019)
To ensure food quality and safety food, professionals need a knowledge of food composition and characteristics. The analysis of food product is required for quality management throughout the developmental process including the raw materials and ingredients, but food analysis adds processing cost for food industry and consumes time for government agencies. Advances in Noninvasive Food Analysis explores the potential and recent advances in non-invasive food analysis techniques used to ensure food quality and safety. Such cost-reducing and time-saving non-destructive food analysis techniques covered include, Infrared, Raman Spectroscopy, and Nuclear Magnetic Resonance. The book also covers data processing and modelling. Features: Covers the advent of non-invasive, non-destructive methods of food analysis Presents such techniques as near and mid infrared, Raman Spectroscopy, and Nuclear Magnetic Resonance Describes the growing role of nanotechnology in non-invasive food analysis Includes image analysis and data processing and modelling required to sort out the data The prime for this book are food professionals working in industry, control authorities and research organizations that ensure food quality and safety as well as libraries of universities with substantial food science programs, food companies and food producers with research and development departments. Also available in the Contemporary Food Engineering series: Advances in Food Bioproducts, Fermentation Engineering and Bioprocessing Technologies , edited by Monica Lizeth Chavez Gonzalez, Nagamani Balagurusamy, Christobal N. Aguilar (ISBN 9781138544222) Advances in Vinegar Production, edited by Argyro Bekatorou (ISBN 9780815365990) Innovative Technologies in Seafood Processing, edited by Yesim Ozogul (ISBN 9780815366447)
OCLC-licensed vendor bibliographic record.
Keywords: Food -- Analysis; Food -- Nondestructive testing; SCIENCE / Chemistry / Analytic; TECHNOLOGY / Food Science